THE ETHICO-CULTURAL IMPLICATIONS OF ARTIFICIAL INTELLIGENCE AND ALGORITHM-GENERATED MUSIC IN NIGERIA - Peter O. O. Ottuh, Doris Udoka Uti and Margaret A. Efurhievwe (Journal of Dharma, 2024)
AI technologies are increasingly shaping creative processes in the music industry, raising critical ethical and cultural questions about ownership, originality and the value of human artistry. In Nigeria, the rise of AI-driven music presents challenges in preserving cultural authenticity and protecting intellectual property rights amid rapid technological advancements. This study critically examines the ethical and cultural implications of AI-generated music within the context of Nigerian music production. Using descriptive and evaluative methods—including literature reviews, interviews, case studies and content analysis—it explores industry perspectives, concerns and the practical impact of these technologies. Findings reveal that AI blurs the lines between human and machine creativity, contributes to cultural homogenization and threatens job security for musicians and producers. Additional ethical concerns include potential loss of intellectual property and copyright protections.